Characterisation of human tissues analogues for ballistic testing - Appleby-Thomas, Gareth J.; Khan, Irfan; Painter, Jonathan; Zioupos, Peter; Lordachescu, Alexandra; Hes, Roelof A. G. (None - paper only available to conference delegates, 2023)
Ballistic testing necessarily employs simulant target materials for ethical and fiscal reasons. Current tissue analogues utilised for ballistic testing / research are, however, typically relatively simplistic – such as ballistics soap or gelatin. Consequently, these materials are seldom representative of complex mammalian constructs. In this paper the authors have drawn together core elements of previously published in-house research with the aim of providing insight into potential approaches to create a composite simulant solution. In particular, tissue analogues covering the epidermal, epithelial, connective, muscular and skeletal components are presented. These results highlight the complementary nature of employing a range of tissue simulant materials and, in parallel, the importance – if ballistic testing data is to be truly representative – of fully understanding the nature of the analogues employed.